Accounting practices and charitable giving: Integrating Maqasid al-Shariah framework for Tabung Masjid in Malaysia - Zakariyah, Luqman; Mohd Noor, Azman; Sarif, Suhaimi Mhd (Serials Publications Pvt. Ltd, 2017)
Purpose: Mosques play a vital role in strengthening Islamic values among community members through programs and activities. An appropriate amount of funding is required to carry out such activities. This paper focuses on the ability of appropriate accounting practices in ensuring increased donations that will enable mosques to practice the Maslahah principles of Maqasid, i.e. ensuring public interest. Methodology: This paper proposed a conceptual model to analyse the impact of accounting practices on donations by stewardship and resource-based theory. The sample of 287 respondents consists of key personnel of Tabung Masjid in Malaysia. Structural equation modelling was used to test the validity of the proposed model. Findings: The main findings of this paper show that governance mechanisms influence reporting and individual donations. Reporting practices do not have a mediating effect, but indirectly affect the relationships between governance mechanisms and individual donations in Tabung Masjids. A negative association between governance mechanisms and donations indicates that higher level of internal auditing reduces public trust in mosques which results in decreased donations. Transparent reporting practices, on the other hand, have a positive influence on donations. Research Limitations: This study has focused only on one aspect of governance mechanism (auditing), but several other internal governance mechanisms could provide better estimates. Practical Implications: The results indicate the significance of external auditing and reporting that may increase individual donations in mosques. Thus, from a policy perspective, bodies that regulate mosques in Malaysia should consider implementing appropriate governance and disclosure mechanisms in order to increase the ability of mosques in serving public interests. Originality: To date, this is the first research that has been conducted to analyse the impact of governance mechanisms on reporting and donations in the context of mosques in Malaysia. The study also validates the applicability of stewardship theory in studying Islamic Religious Charitable Institutions.